LANGKAH-LANGKAH EFEKTIF DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QUR'AN - Anni Malihatul Hawa; Aisah Sumaiyah Siregar; Salmiah; Baiq Siti Hajar (Yayasan Baitul Hikmah al-Zain, 2025)
This research aims to identify and analyze effective methods in improving Qur'anic memorization abilities. Using a qualitative approach with case study methodology, the research was conducted in three tahfidz Islamic boarding schools in Central Java, involving 60 students and 12 tahfidz teachers as respondents. Data was collected through participatory observation, in-depth interviews, and documentation over six months. The results revealed five effective steps in enhancing memorization ability: (1) implementation of the talaqqi method with systematic repetition, (2) utilization of mushaf visualization techniques for spatial memory reinforcement, (3) implementation of structured schedules with optimal time distribution between memorization and muraja'ah, (4) utilization of audio-visual technology as memorization aids, and (5) formation of peer-teaching study groups. The memorization success rate increased by 40% after implementing these methods, with retention reaching 85% in the three-month post-implementation evaluation. This research contributes to the development of more effective Qur'anic memorization learning methodologies that are adaptive to modern learning needs.